Sex differences in treatment and outcomes of patients with in‐hospital ST‐elevation myocardial infarction. Issue 4 (7th March 2022) - Stehli, Julia; Dinh, Diem; Dagan, Misha; Dick, Ron; Oxley, Stephanie; Brennan, Angela; Lefkovits, Jeffrey; Duffy, Stephen J.; Zaman, Sarah
Abstract: Background and Hypothesis: Two cohorts face high mortality after ST‐elevation myocardial infarction (STEMI): females and patients with in‐hospital STEMI. The aim of this study was to evaluate sex differences in ischemic times and outcomes of in‐hospital STEMI patients. Methods: Consecutive STEMI patients treated with percutaneous coronary intervention (PCI) were prospectively recruited from 30 hospitals into the Victorian Cardiac Outcomes Registry (2013−2018). Sex discrepancies within in‐hospital STEMIs were compared with out‐of‐hospital STEMIs. The primary endpoint was 12‐month all‐cause mortality. Secondary endpoints included symptom‐to‐device (STD) time and 30‐day major adverse cardiovascular events (MACE). To investigate the relationship between sex and 12‐month mortality for in‐hospital versus out‐of‐hospital STEMIs, an interaction analysis was included in the multivariable models. Results: A total of 7493 STEMI patients underwent PCI of which 494 (6.6%) occurred in‐hospital. In‐hospital versus out‐of‐hospital STEMIs comprised 31.9% and 19.9% females, respectively. Female in‐hospital STEMIs were older (69.5 vs. 65.9 years, p  = .003) with longer adjusted geometric mean STD times (104.6 vs. 94.3 min, p  < .001) than men. Female versus male in‐hospital STEMIs had no difference in 12‐month mortality (27.1% vs. 20.3%, p  = .92) and MACE (22.8% vs. 19.3%, p  = .87). Female sex was not independently associated with 12‐month mortality for in‐hospital STEMIs which was consistent across the STEMI cohort (OR: 1.26, 95% CI: 0.94–1.70, p  = .13). Conclusions: In‐hospital STEMIs are more frequent in females relative to out‐of‐hospital STEMIs. Despite already being under medical care, females with in‐hospital STEMIs experienced a 10‐min mean excess in STD time compared with males, after adjustment for confounders. Adjusted 12‐month mortality and MACE were similar to males.